2014
DOI: 10.1007/s11095-014-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Permeability and Growth-Inhibitory Properties of Gonadotropin-Releasing Hormone Liposaccharides

Abstract: These results indicated lipidation and glycosylation improves the druggability of GnRH and could lead to an increased direct antitumour activity in some hormone dependent and independent reproductive cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…; Goodwin et al. ). Although the effects of lipidation of a parent molecule on blood–brain barrier (BBB) penetration have not been documented, hydrophobic small molecules with a higher log‐ P values show better penetration across the BBB compared to their parental hydrophilic congeners (Egleton and Davis ).…”
Section: Introductionmentioning
confidence: 99%
“…; Goodwin et al. ). Although the effects of lipidation of a parent molecule on blood–brain barrier (BBB) penetration have not been documented, hydrophobic small molecules with a higher log‐ P values show better penetration across the BBB compared to their parental hydrophilic congeners (Egleton and Davis ).…”
Section: Introductionmentioning
confidence: 99%
“…The lipopeptide conjugates enhance the membranelike characteristics of the peptides due to their lipid nature 2 . Enhancement of metabolic stability and membrane permeability at the same time could considerably contribute to improvement in the bioavailability of peptides 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that lipid-modified luteinizing hormone-releasing hormone (LHRH, also known as gonadotropin-releasing hormone, GnRH) peptides served as effective prodrugs for the release of the parent peptide 4,8 . It was shown that one stereoisomer of the lipid was cleaved very rapidly, providing a large amount of the parent peptide while the opposite stereoisomer was cleaved much more slowly and providing prolonged increase in the LHRH peptide concentration 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the nasal route might potentiate the accumulation of the brain permeable peptide with a long half-life in circulation, resulting in brain levels that reach 1-2% of the dose administered. The diffusion of therapeutic peptides (<10 kDa) into the extracellular brain parenchyma, such as that described here, is not restricted significantly when compared to that of larger neurotrophic factors like neurotrophins, PDGF (platelet-derived growth factor) and CNTF (ciliary neurotrophic factor) which approach the dimensions of the extracellular space (15-20 nm in diameter) (39). The clearance of the peptides in the target organ is also an essential feature, as this will permit the degradation of the therapeutic peptides into elements that are naturally present in the brain parenchyma (40).…”
Section: Discussionmentioning
confidence: 87%